Application of Subperineural Resection Technique in Vestibular Schwannomas: Surgical Efficacy and Outcomes in 124 patients - Wu, Yingxi; Wei, Chen; Wang, Ping; Zhang, Yunze; Wu, Yang; Xue, Yafei; Zhao, Tianzhi; Qu, Yan (Frontiers in Oncology, 2022)
Objective We aimed to explore the application and prospects of the subperineural resection technique for tumor separation and removal under the perineurium during surgery for vestibular schwannomas (VSs). Methods This study retrospectively analyzed 124 patients with VSs who underwent surgery via a retrosigmoid approach from July 2015 to October 2020 in the Department of Neurosurgery, Tangdu Hospital, Air Force Military Medical University. The data will be discussed with regard to the following aspects: clinical features, surgical strategies, tumor resection extent, facial–acoustic function preservation, and postoperative complications. Results Gross total resection (GTR) of the tumor was achieved in 104 patients, with a GTR rate of 83.9%, and subtotal resection (STR) of the tumor was achieved in 20 patients. There was no significant difference in facial and acoustic nerve functional preservation between GTR and STR, as well as in tumor resection between solid and cystic tumors. The retention rate reached 97.6% in terms of complete anatomical facial nerve preservation. Facial nerve function was assessed using the House–Brackmann (HB) grading score. Consequently, HB grades of I–II, III–IV, and V–VI were determined for 96 (77.4%), 25 (20.2%), and 3 (2.4%) cases, respectively, 1 week postoperatively and accounted for 110 cases (88.7%), 13 cases (10.5%), and 1 case (0.8%), respectively, at 6 months. Fifteen of 35 (42.9%) patients with serviceable hearing before the operation still had serviceable hearing at 6 months postoperatively. There were 5 cases of cerebellar or brainstem bleeding after the operation, and one patient died. Multivariate logistic regression analysis showed that older age (≥60 years, p = 0.011), large tumor (>3 cm, p = 0.004), and cystic tumor (p = 0.046) were independent risk factors associated with the extent of adhesion between the tumor and the brainstem and facial–acoustic nerve. Conclusion We successfully applied the subperineural resection technique to a large series of patients with VSs and achieved satisfactory results. Accurate identification of the perineurium and subperineural resection of the tumor can effectively reduce the disturbance of the facial–acoustic nerve during the operation and provide an intuitive basis for judging the tumor boundary. The subperineural resection technique may be conducive to improving the rate of total tumor resection and facial–acoustic nerve functional preservation in the surgical treatment of VSs.